Towards Industrial Ecology: An Assessment Of Environmental Practices Within The Plastic Industry In Accra, Ghana - Gyabo, S.O. (University of Ghana, 2021)
The purpose of this study is to assess corporate environmental practices being implemented by plastic producing enterprises in Accra, Ghana. The study explores existing environmental practices at the enterprise level, examines the level of compliance with environmental regulations by plastic producing enterprises, examines perception of plastic producing enterprises on the influence of growing activism against plastic pollution from the public on their strategies and the opportunities and challenges of using industrial ecology to achieve sustainable plastic production and consumption in relation to sustainable development goal 12 (responsible production and consumption). The study employed methodological triangulation on data obtained from 18 plastic-producing enterprises within the Accra and Tema Metropolis in Ghana through questionnaire survey and informal interviews. Data was analysed quantitatively and supported with qualitative data. It was revealed that enterprises engage in environmental practices such as recycling, adoption of sustainable technology and environmental management systems (EMS), use of recycled materials, and energy efficiency. Compliance with environmental regulation was found to be high amongst enterprises with 17 of 18 enterprises having met regulatory requirements and therefore certified by the regulatory body (EPA). Further, enterprises did not perceive reduced sales and profits over the last 10 years though raw materials were perceived to have become more expensive due to scarcity of resources from the natural environment. Firms also professed to putting in measures to improve their reputation in the face of the public as a result of public activisms on plastic pollution. Additionally, existing national plastic management policy (NPMP), recycling, sustainability reporting and education and awareness provides opportunity for industrial ecology to be used to achieve sustainable plastic waste management, though some challenges in these areas persist. Ecosystem principles of roundput, was being implemented by majority of enterprises through engagement in recycling and locality principle was being implemented by a few enterprises. Situating the study within the institutional theory, enterprises had normative, regulatory and cognitive reasons for engaging in environmental practices. Whereas based on the natural resource-based view (NRBV), enterprises derived competitive advantage in the form of improved efficiency and reduced cost of production, differentiation benefit and access to international markets, which were achieved through the product stewardship, pollution prevention and sustainable development practices being accomplished by enterprises.
MPhil. Sustainability Science
Keywords: Plastic Industry; Industrial Ecology; Ghana; Accra